2022
DOI: 10.3389/fped.2022.1001565
|View full text |Cite
|
Sign up to set email alerts
|

Comparing outcomes between culture-positive and culture-negative septic shock in a PICU: A retrospective cohort study

Abstract: BackgroundWe assessed the outcomes and characteristics of culture-negative septic shock (CNSS) and culture-positive septic shock (CPSS) in pediatric intensive care unit (PICU).MethodsWe performed a retrospective study on the data of children admitted to the PICU due to septic shock between January 2018 and December 2021. The primary outcome was in-hospital mortality. The secondary outcomes were the length of stay (LOS) of hospital, the need for mechanical ventilation (MV) and continue renal replacement therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Full texts of 18 studies were retrieved and assessed for eligibility criteria. Overall, 10 studies met the inclusion criteria [6][7][11][12][13][14][15][16][17][18] and were included in the meta-analysis involving 23,973 patients. The characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Full texts of 18 studies were retrieved and assessed for eligibility criteria. Overall, 10 studies met the inclusion criteria [6][7][11][12][13][14][15][16][17][18] and were included in the meta-analysis involving 23,973 patients. The characteristics of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Table 1. The majority of the included studies were retrospective cohorts [7,[11][12][13][14][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While many studies compared the clinical features between CPSS and CNSS in adult patients, only few studies directly compared the two groups in the pediatric population [16][17][18]. In addition, the relationship between clinical characteristics and proven bacteria is not well-studied in pediatric patients with septic shock.…”
Section: Introductionmentioning
confidence: 99%